Social Conflict in Thailand: an Impact of Changing Media Landscape - LT. Gen. Perapong Manakit, Ph.D.; Nattawan Auscharnuwat (Journal of Digital Communications, 2020)
This article aims to examine Thailand’s recent political conflict and the interplay between the factors that have given rise to the conflict: the pervasion of New Media, the generational experience of its young recipients, the long-lasting impact of Thailand’s biased development strategy, the problematic use of theories in social analysis, and the development of Thai media under capitalism. Each factor is then analyzed by literature review before a conclusion is drawn. The study found that the New Media is responsible of its recipients’ shortened attention span and tendency to making quick judgments. Part of the protesters belongs to a generation predisposed to egocentric worldviews that contributes to their dissatisfaction with Thai society. Their perception of unequal Thai society stems from the contrast between urban and rural areas resulting from Thailand’s biased development strategy. The problematic use of micro sociological theories and System Theory in social analysis, lacking macro perspective, also led the protesters to view Thai society as divided into upper and lower class. In addition, the development of Old Media under capitalism made it incapable of catering to the content demands of Thai middle class and thus turning young adults further away from Old Media to the New Media. In light of the findings, the article suggests alleviating the Old Media’s constraints under capitalism and enabling it to improve content quality in order to regain the audience it lost to the New Media, helping digital TV reclaim eyeballs from cable and satellite TV, and promoting quality news coverage.